Immunomodulatory and Antidiabetic Potential of Kratom (Mitragyna speciosa) on Animal Models: Potentials and Future Research - Ilmi, Annisa Nurul; Hasibuan, Febry Rahmadhani; Pujiyanti, Aloysia Sri; Kurniati, Reni (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
Kratom (Mitragyna speciosa) has been traditionally used for its analgesic and stimulant properties. Recent preclinical studies suggesting its potential as an anti-inflammatory and antidiabetic agent. A comprehensive search of PubMed, ScienceDirect, and Google Scholar (2010-2024) using keywords “Kratom”, “inflammation”, and “diabetes” identified 82 studies. After applying inclusion criteria (original research, English/Bahasa Indonesia, in vivo animal models investigating anti-inflammatory/antidiabetic effects) and excluding reviews, in vitro studies, and conference abstracts, 14 studies comprising 9 key articles on the pharmacological activities of Kratom were analyzed. Dosages ranged from 0,5 mg/g to 500 mg/kg across various extraction methods and treatment durations. Studies show that Kratom extracts can inhibit pro-inflammatory cytokines (IL-1β, TNF-α) via NF-κB, COX-2, and MAPK/ERK pathways. In diabetic models, Kratom reduced blood glucose levels by 15-45%, improved glucose tolerance, and enhanced antioxidant status. Aqueous and ethanolic extracts showed comparable efficacy, with optimal effects observed at 100-200 mg/kg doses. Despite these findings, safety concerns remain regarding toxicity, dependence, and drug interactions. Further toxicological studies and clinical trials are essential to validate its therapeutic potential. This review highlights the need for comprehensive research and regulatory evaluation to support the safe medicinal use of Kratom.